2021
DOI: 10.1039/d1ta04736a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydration on ion transport in Li2Sn2S5·xH2O

Abstract: The layered material Li2Sn2S5 forms two hydrated solid phases under increasing humidity. Intercalated water hydrates the interlayer Li+ ions and screens coulombic interactions, leading to a high in-plane mobility of both Li+ and H2O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…81,82 Furthermore, Zn conduction and the effect of hydration for cation conduction in the monovalent cation of Li have been attracting attention. [83][84][85] For instance, Joos et al determined the relationship between the number of H 2 O molecules and Li transport in Li 2 Sn 2 S 5 $nH 2 O and demonstrated that the transport rate considerably increased up to x z 8 with increasing hydration. 84 In complex hydride solid electrolytes, Takano et al discovered that hydrated LiBH 4 exhibited a considerably higher electrical conductivity (4.89 × 10 −4 S cm −1 ) than LiBH 4 at 45 °C.…”
Section: Solid-state Zn 2+ Ionic Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 Furthermore, Zn conduction and the effect of hydration for cation conduction in the monovalent cation of Li have been attracting attention. [83][84][85] For instance, Joos et al determined the relationship between the number of H 2 O molecules and Li transport in Li 2 Sn 2 S 5 $nH 2 O and demonstrated that the transport rate considerably increased up to x z 8 with increasing hydration. 84 In complex hydride solid electrolytes, Takano et al discovered that hydrated LiBH 4 exhibited a considerably higher electrical conductivity (4.89 × 10 −4 S cm −1 ) than LiBH 4 at 45 °C.…”
Section: Solid-state Zn 2+ Ionic Conductivitymentioning
confidence: 99%
“…[83][84][85] For instance, Joos et al determined the relationship between the number of H 2 O molecules and Li transport in Li 2 Sn 2 S 5 $nH 2 O and demonstrated that the transport rate considerably increased up to x z 8 with increasing hydration. 84 In complex hydride solid electrolytes, Takano et al discovered that hydrated LiBH 4 exhibited a considerably higher electrical conductivity (4.89 × 10 −4 S cm −1 ) than LiBH 4 at 45 °C. 85 As with these materials, the effects of H 2 O exchange in ZnB 12 H 12 $12H 2 O can be of signicance for Zn 2+ conduction.…”
Section: Solid-state Zn 2+ Ionic Conductivitymentioning
confidence: 99%
“…31 Besides that, the presence of water in its crystal structure may also assist the Li + transport through the high-symmetry cubic polymorph. 41,69 It has already been reported that hydrated LiBH 4 can exhibit higher ionic conductivity than anhydrous LiBH 4 , and that enhancement of Li + conduction might be associated to the motion of structural water. 41 In a similar manner, the presence of ammonia molecules in hemi-ammine lithium borohydride (LiBH 4 $1/2NH 3 ) assists the migration of Li + through the crystal structure, increasing its ionic conductivity.…”
Section: Sample Characterisationmentioning
confidence: 99%
“…Closo -type complex hydrides (CTCHs) arise as a class of promising solid-state battery electrolytes because of their relatively facile cation diffusion compared to many other materials . Interestingly, recent experiments showed that adding neutral molecules into the lattice of CTCH electrolytes in the synthetic process can significantly promote cation diffusion, which in turn can promote the battery performance. As summarized in Figure , though divalent CTCHs generally have larger diffusion activation energies than monovalent CTCHs, the addition of neutral molecules (in particular, water molecules) endows them with new hope by pressing their barriers to reach the upper limits of monovalent CTCHs. Nevertheless, the structure-performance relationships of these neutral molecules containing divalent CTCHs remained as a “black box”, as limited by the structural characterization techniques to date.…”
Section: Introductionmentioning
confidence: 99%